Role of Dividend Payout, Retained Earnings, and Market Conditions in Firm Reputation - Muhammad Hasnain Ali; Muhammad Abdullah; Shan Ali (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2024)
This study explores the influence of dividend payout, retained earnings, and market conditions on firm reputation, a critical intangible asset that significantly impacts stakeholder trust and investment decisions. Dividend payout is examined as a measure of shareholder value distribution, while retained earnings reflect a firm’s internal growth strategies. Market conditions act as an external factor influencing public perception and corporate performance. This study employs a quantitative research design using secondary data from publicly traded companies spanning five years. Structural Equation Modeling (SEM) is employed for data analysis to determine the relationships between variables and their statistical significance. The results reveal that dividend payout has a positive and significant impact on firm reputation. Retained earnings show a dual effect, with higher reserves signaling stability and growth but sometimes raising concerns about insufficient shareholder returns. Market conditions moderate these relationships. Companies must balance dividend payouts and retained earnings to maintain investor trust and fund growth initiatives. Additionally, firms should remain agile in adapting to fluctuating market conditions to safeguard their reputations. These insights offer valuable guidance for financial managers, policymakers, and investors aiming to optimize firm reputation as a competitive advantage